Biting midges of the genus Atrichopogon Kieffer (Diptera: Ceratopogonidae) described by Kieffer from Taiwan - Szadziewski, Ryszard; Dominiak, Patrycja (Zootaxa, 2009)
Twelve species of biting midges of the genus Atrichopogon reported by Kieffer (1912, 1916a,b, 1921, 1922) from Taiwan are redescribed, illustrated and/or interpreted. They are included in the subgenus Psilokempia Enderlein (A. myrmedon Kieffer, 1912) and in the subgenus Atrichopogon s. str. (A. argus Kieffer, 1916, A. flaviceps Kieffer, 1912, A. haemorrhoidalis Kieffer, 1921, A. insularis Kieffer, 1921, A. minimus Kieffer, 1916, A. pruinosus Kieffer, 1921 and A. ruber Kieffer, 1916). Five new synonyms are proposed for the following species: A. ruber Kieffer, 1916 (=A. formosanus Kieffer 1918), A. myrmedon Kieffer, 1922 (=A. quadrispinosus Remm, 1993; =A. pectinacaudalis Yu & Yan, 2006), A. insularis Kieffer, 1921 (=A. citrinipes Kieffer, 1922) and A. flaviceps Kieffer, 1912 (=A. mendax Kieffer, 1922, as var. of A. flaviceps). Atrichopogon crispantis Liu, Yan & Liu, 1996 is resurrected from synonymy with A. insularis Kieffer, 1921. Atrichopogon rufescens Kieffer, 1921 is recognized as a nomen dubium, while A. atriceps mentioned by Blech & Rohlfien (1987) is considered a nomen nudum. A key to the species described by Kieffer from Taiwan is provided.